2021
DOI: 10.1515/opag-2021-0214
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and structure of acorn starches isolated by enzymatic and alkaline methods

Abstract: Morphology and structure of starch from fruits of two acorns species, Quercus rotundifolia Lam. (QR) and Quercus suber Lam. (QS), isolated by enzymatic (ENZ) and alkaline (A3S) methods were studied. Acorn starches granules presented a round and oval shape, consisting of medium/small granules, with a mean granule size ranging between 9 and 13 µm. Isolated acorn starches appear as light grayish-brown in naked eye, with high values of L* for starches isolated by the ENZ method, and QR starches were duller than QS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 42 publications
2
16
0
Order By: Relevance
“…The satisfactory yield of EAE can be attributed to the efficiency and specificity of the enzyme to digest the proteins attached to a surface of starch granules and interrupt the starch–protein interactions. [ 19,20,34 ] In WME and EAE method the maximum yield was obtained in B‐level (i.e., WME‐B and EAE‐B). It was suggested that suitable treatment time and higher acid concentration increase the starch yield and purity by decreasing the protein level of the isolated starch.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The satisfactory yield of EAE can be attributed to the efficiency and specificity of the enzyme to digest the proteins attached to a surface of starch granules and interrupt the starch–protein interactions. [ 19,20,34 ] In WME and EAE method the maximum yield was obtained in B‐level (i.e., WME‐B and EAE‐B). It was suggested that suitable treatment time and higher acid concentration increase the starch yield and purity by decreasing the protein level of the isolated starch.…”
Section: Resultsmentioning
confidence: 99%
“…[ 10 ] EAE method also can preserve the structure of the starch with selective proteolytic action. [ 34 ]…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations